Genetic Polymorphisms in the RAD51 Gene with a Risk of Head and Neck Cancer and Esophageal Cancer: A Meta-Analysis - Lin Li; Xue Zhang; Zhong-Ti Zhang (International Journal of Genomics)
Background. The role of RAD51 gene polymorphisms with the development of head and neck cancer (HNC) and esophageal cancer (EC) remains controversial. This meta-analysis was conducted to evaluate the correlation between the RAD51 polymorphisms and these two cancers quantitatively. Methods. Databases of PubMed, Web of Science, and Embase were used to search relevant papers prior to August 17, 2019. STATA 11.0 was performed to observe the correlation. Results. Ten relevant papers were enrolled in our analysis. Overall, a significant correlation was observed between the rs1801320 polymorphism and the increased risk of these two cancers (OR=1.32, 95%CI=1.03‐1.71 for C vs. G; OR=1.50, 95%CI=1.03‐2.19 for CG vs. GG; and OR=1.44, 95%CI=1.05‐1.99 for CC+CG vs. GG). In subgroup analyses, an increased risk was found for EC (OR=2.07, 95%CI=1.01‐4.25 for C vs. G; OR=2.08, 95%CI=1.17‐3.71 for CC vs. GG; and OR=1.78, 95%CI=1.00‐3.15 for CC vs. CG+GG), but not for HNC. Moreover, our analysis revealed that no statistical evidence of correlation was discovered between the polymorphism of rs1801321 and the increased risk of HNC. However, stratified analysis based on ethnicity suggested that rs1801321 polymorphism was related to the decreased risk of HNC among Caucasians (OR=0.82, 95%CI=0.72‐0.95 for T vs. G). Conclusions. rs1801320 polymorphism was strongly associated with the risk of these two associated cancers, especially with esophageal cancer. Moreover, our results revealed that rs1801321 polymorphism was correlated to the decreased risk of HNC among Caucasians.